Chromium (VI) induced oxidative stress in halotolerant alga Dunaliella salina and D. tertiolecta isolated from sambhar salt lake of Rajasthan (India) - Arun, N.; Vidyalaxmi, Vidyalaxmi; Singh, D. P. (Cellular and Molecular Biology, 2014)
Chromium (Cr) is one of the most serious pollutants in aquatic systems. This study was performed to understand the effect of Cr (VI) on halophilic algal strains of D. salina and D. tertiolecta. The results revealed good tolerance of D. salina towards chromium (VI) up to 8 ppm concentration, whereas tolerance level in D. tertiolecta was up to 2 ppm concentration. Cr (VI) not only inhibited the growth of D. tertiolecta, but also showed increased inhibition in the level of photosynthetic pigments, protein and carbohydrate. Results have revealed that chromium (VI) induced higher increase in lipid peroxidation and H2O2 production in D. tertiolecta than the D. salina, particularly at higher concentration of chromium (VI). Chromium (VI) induced increase in the rate of RNO bleaching, loss of pigments and thiol (-SH) group was relatively higher in D. tertiolecta than the D. salina, which is indicating that D. tertiolecta was prone to Cr (VI) induced oxidative stress. Results on RNO bleaching in the presence of radical quenchers suggested that OH° radical played an important role in the chromium (VI)-induced general oxidative stress in D. tertiolecta.